Difficulties of Teaching Based on Differentiated Instruction from the Viewpoint of Arabic Language Teachers in Qatif Governorate, Saudi Arabia - Alnasser, Mohammed Abdullah (Journal of Educational and Psychological Sciences, 2020)
The present study aims to identify the Difficulties of Teaching Based On Differentiated Instruction Viewpoint Of Arabic Teachers In Qatif Governorate In the Kingdom of Saudi Arabia. In order to achieve these objectives, a questionnaire was designed, It consisted of (33) items distributed to five Domains. It was distributed to the study Sample wish was formed from (172) Arabic teachers chosen randomly from all study phases. The study found that the whole mean of Difficulties of Teaching Based On Differentiated Instruction Viewpoint Of Arabic Teachers In Qatif Governorate was (3.60). At the domains level: The difficulties of the environment of the school was the first with a mean (3.97), then the difficulties of a teacher with a mean (3.73).Booth with a high degree of difficulty. Difficulties of Curriculum was the third with a mean of (3.58), Then The difficulties of Administrative Regulation with a mean of (3.43), Finally The difficulties of Students with a mean of (3.28). All final three domains with a Medium degree of difficulty. The study also found that there were no significant differences between the average of these answers at the level of significance (α ≤ 0.05) due to the impact study phase. Based on these results The researcher recommended to train teachers and supply schools with suitable facilities and materials to teach the Arabic language based on Differentiated Instruction.
Keywords: Difficulties of Teaching; Arabic teacher; Differentiated Instruction